ANALISIS EFISIENSI ALOKASI PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI TOMAT DI KECAMATAN KAPONTORI KABUPATEN BUTON - Gusmin Sarif Amane; Bahari Bahari; La Ode Geo (Universitas Halu Oleo, 2019)
This study aims to analyze the factors that influence production and analyze the efficiency of allocation of the use of production factors on tomato farming conducted in Kapontori District, Buton Regency. Data collection was conducted in January-April 2019 with the survey method. A total of 67 tomato farmers were selected as samples using the simple random sampling method. Data were analyzed using multiple nonlinear regression with Cobb-Douglas production function followed by calculation of price efficiency. The results showed that the area of land, seeds, and fertilizers were factors of production which had a significant effect on tomato production. Tomato farming is on an increasing return to scale scale where increasing use of factors in the production of land, seeds, fertilizers, pesticides and labor simultaneously leads to a greater increase in tomato production. Production factor allocation efficiency analysis shows that the use of production factors in land area is not efficient so it needs to be added, the use of seed production factors is not efficient so it needs to be added, and the use of fertilizer production factors is inefficient so it needs to be reduced.Keywords: efficiency; production factors; tomatoes